2020
DOI: 10.1021/acs.joc.0c01867
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of the Southern Hemisphere of Spirastrellolide A and Analogues

Abstract: The synthesis and biological evaluation of truncated spirastrellolide A analogues comprised of the southern hemisphere against protein phosphatase 2A are described. A convergent synthesis was designed featuring two gold-catalyzed cyclization reactions, specifically, a dehydrative cyclization of monoallylic diols for the synthesis of the tetrahydropyran (A-ring) and a regioselective spiroketalization for the efficient generation of the [6,6]-spiroketal (B, C-ring system). The synthesis of the southern hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…However, these contributions merely focused on reaching the final polyketide structure and, in scarce examples, probed their PP2A inhibitory action, without realizing that small fragments lacking the C1-C15 moiety might exert an allosteric activation. Recently, Aponick and co-workers described the synthesis of Spirastrellolide A analogues with high structural similarity to OA fragments [82]. Besides the extensive synthetic work, these authors reported maximal PP2A inhibitory activities of several derivatives of about 20% when tested at concentrations as high as 30 μM.…”
Section: Discussionmentioning
confidence: 99%
“…However, these contributions merely focused on reaching the final polyketide structure and, in scarce examples, probed their PP2A inhibitory action, without realizing that small fragments lacking the C1-C15 moiety might exert an allosteric activation. Recently, Aponick and co-workers described the synthesis of Spirastrellolide A analogues with high structural similarity to OA fragments [82]. Besides the extensive synthetic work, these authors reported maximal PP2A inhibitory activities of several derivatives of about 20% when tested at concentrations as high as 30 μM.…”
Section: Discussionmentioning
confidence: 99%